Impact Health Promotion Strategy and Role Local Wisdom in the Implementation of Integrated Management of Childhood Illnesses (IMCI): A Systematic Review (International Journal of Environmental Sciences, 2025)
Background : Integrated Management of Childhood Illness (IMCI)) is needed to prevent mortality rate under five years old in sub-Saharan African and South Asian countries with occurring 11 million annually, due from diarrhea, pneumonia, measles, malnutrition, and newborn care problems. This study aimed to asses health promotion strategies in the process implementation of integrated management of childhood illnesses (IMCI). Methods: The research design uses a systematic review, namely library research, that examines critical quality health journals, which inclusion criteria have filtered. It uses several Google Scholar, PubMed, Science Direct, and Research Gate databases as literacy in this study. There are 718 results according to integrated management of childhood illnesses (IMCI) keywords, which were screened into 28 journals in accordance theme and analyzed with the approach of using the promotion strategy health in the implementation of integrated management of childhood illnesses (IMCI). Finding: Research results show that a health promotion strategy is needed to implement an integrated management of childhood illnesses (IMCI) policy to reduce mortality and morbidity rates.Interpretation: The review suggests that a comprehensive approach to child health, which includes both the prevention and treatment of illnesses, is essential for improving child health outcomes. Health promotion strategies play a critical role in this approach and can lead to significant improvements in child health when implemented effectively.